2018
DOI: 10.1177/1756284818777943
|View full text |Cite
|
Sign up to set email alerts
|

Proton-pump inhibitors among adults: a nationwide drug-utilization study

Abstract: Background:The use of proton-pump inhibitors (PPIs) has grown worldwide, and there are concerns about increased unsubstantiated long-term use. The aim of the study was to describe the real-world use of PPIs over the past decade in an entire national population.Methods:This was a nationwide population-based drug-utilization study. Patterns of outpatient PPI use among adults in Iceland between 2003 and 2015 were investigated, including annual incidence and prevalence, duration of use, and dose of tablet used (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
2
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 41 publications
6
114
2
8
Order By: Relevance
“…PPIs have become one of the best-selling drug classes in many countries [15][16][17][18]. PPI use is also increasing in Japan, with an annual expenditure in 2017 that was estimated at 268 billion yen [19].…”
Section: Discussionmentioning
confidence: 99%
“…PPIs have become one of the best-selling drug classes in many countries [15][16][17][18]. PPI use is also increasing in Japan, with an annual expenditure in 2017 that was estimated at 268 billion yen [19].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] A UK and a Iceland case-control study found the cancer risk was not associated with using PPIs. 8,9 The novelty in our study is that both study cohorts were peptic ulcer patients who were homogenous in comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Because PPIs could potentially enhance anti‐tumor chemotherapy, it has also been suspected that these medicines may play a role in preventing tumor development . We hypothesized that PPIs usage in women with peptic ulcer might have a lower risk of breast cancer.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Third, in 2009 low‐dose PPIs became available over‐the‐counter (OTC) in Iceland, and OTC use is not recorded in the Medicine Registry. This may have led to some misclassification of PPI use in our study but is unlikely to have impacted the results much as the amount of OTC use was relatively low during the study period, ranging from 1% to 10% of total PPI volume sold annually in 2009 to 2014 . Another misclassification of PPI exposure might has modestly biased the study results since we did not have information on PPI use prior to 2003, causing some potential PPI users before 2003 to be considered as never users.…”
Section: Discussionmentioning
confidence: 99%